2004
DOI: 10.1007/s10896-004-0679-4
|View full text |Cite
|
Sign up to set email alerts
|

Humiliation, Manipulation, and Control: Evidence of Centrality in Domestic Violence Against an Adult Partner

Abstract: This paper describes two related studies. Study 1 is a literature review of existing adult partner domestic violence assessment scales. Results of the review revealed that the scales varied on the available amount of empirical evidence for validity and reliability. More importantly, results showed that the content of the scales focused most heavily on the physical abuse aspects of domestic violence. Study 2 is a factor analysis performed on the results of 64 items taken from the Artemis Intake Questionnaire, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…The use of nonphysical violence in abusive relationships is well established in the literature (Strauchler et al 2004;Margolin et al 1998;Kaukinen 2004;Felson and Messner 2000;Outlaw 2009;Schwartz 2005). We argue, however, that research on emotional abuse and controlling behaviors can be advanced by simultaneously examining factors such as employment compatibility and alcohol consumption by both the offender and the victim.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The use of nonphysical violence in abusive relationships is well established in the literature (Strauchler et al 2004;Margolin et al 1998;Kaukinen 2004;Felson and Messner 2000;Outlaw 2009;Schwartz 2005). We argue, however, that research on emotional abuse and controlling behaviors can be advanced by simultaneously examining factors such as employment compatibility and alcohol consumption by both the offender and the victim.…”
mentioning
confidence: 83%
“…Particularly, scholars of domestic violence have documented the complex nature of abusive relationships, including physical, emotional, and controlling abuse, eco-nomic maltreatment, or any combination of these acts (Strauchler et al 2004;Outlaw 2009). Early studies utilizing the then-newly created Conflict Tactics Scale (Straus 1979) focused on physical violence (i.e., slapping, punching, kicking, etc.…”
mentioning
confidence: 99%
“…For example, Strauchler et al (2004) conducted a comprehensive review of 21 measures of partner violence and concluded that -results of this factor analysis suggest that greater emphasis must be put on factors other than physical violence in the construction of future domestic violence scales‖ (p. 339). Notably, their review found that limited emphasis was placed on psychological aspects of partner violence such as humiliation, psychological manipulation, and control (Strauchler et al, 2004). Similarly, Schwartz et al (2012) concluded from a comprehensive review of existing measures that none was based -on extant theory of how male socialization specifically contributes to dating violence‖ (p. 1962).…”
Section: Rationale For Bereviwos and Gestabementioning
confidence: 99%
“…A comprehensive review of the literature was conducted to identify and develop a preliminary pool of items for inclusion in the scale (e.g., (Burt, 1980;Strauchler et al, 2004)). Of particular relevance was the comprehensive review and compilation of measures of partner violence (Basile et al, 2007;Flood, 2008).…”
Section: Item and Questionnaire Developmentmentioning
confidence: 99%
“…Virtually all domestic violence research and intervention is predicated on this model. Among the several dozen domestic violence assessment tools available that have been tested for construct validity, only a handful consider aspects of abuse other than violence (Strauchler et al, 2004;. All are scaled to reflect the array of violent tactics, and=or the frequency of their use, and physical or psychological effects.…”
Section: Child Exposurementioning
confidence: 99%